2022
DOI: 10.3897/lamo.2.78721
|View full text |Cite
|
Sign up to set email alerts
|

Graphological and semantic foregrounding as affecting gaze and speech of impulsive and reflective readers

Abstract: The study explores the effects of graphological and semantic foregrounding on speech and gaze behavior in textual information construal of subjects with higher and lower impulsivity. Eye movements of sixteen participants were recorded as they read drama texts with interdiscourse switching (semantic foregrounding), with features of typeface distinct from the surrounding text (graphological foregrounding). Discourse modification patterns were analyzed and processed in several steps: specification of participant/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Still, we specified the foregrounding cues which produced higher gaze costs: first letter capitalization, tabulation, full stop, comma, dots, colon. We hypothesized that initial or final discursive act foregrounding cues make information more accessible for the impulsive readers, which conforms to the results received in the previous research [10]. Linguistic foregrounding does not produce such significant effects.…”
Section: Foregrounding and Accessibility With Impulsive Readerssupporting
confidence: 79%
See 1 more Smart Citation
“…Still, we specified the foregrounding cues which produced higher gaze costs: first letter capitalization, tabulation, full stop, comma, dots, colon. We hypothesized that initial or final discursive act foregrounding cues make information more accessible for the impulsive readers, which conforms to the results received in the previous research [10]. Linguistic foregrounding does not produce such significant effects.…”
Section: Foregrounding and Accessibility With Impulsive Readerssupporting
confidence: 79%
“…For instance, in [24; 28] the readers' cognitive style explored via impulsivity and reflectivity was reported to have affected the reaction time and the number of errors made. In [10] it was found that impulsive readers' gaze behavior as opposed to the gaze behavior of reflective readers was more affected by graphological foregrounding cues, which was attributed to the differences in their attention types, bottom-up and top-down attention, consistent with the notion of the impulsive-reflective cognitive style [23]. Overall, the impulsive and reflective styles are treated as a "property of the cognitive system that combines individuals' decision-making time and their performance in problem-solving situations, which involve a high degree of uncertainty" [24: 451].…”
Section: Foregrounding and Accessibility In Cognitive Psychologymentioning
confidence: 99%